Case report Case report of an adolescent girl with limb-girdle muscular dystrophy type 2B – the usefulness of muscle protein immunostaining in the diagnosis of dysferlinopathies - Szymanska, Sylwia; Rokicki, Dariusz; Karkucinska-Wieckowska, Agnieszka; Szymanska-Debinska, Tamara; Ciara, Elzbieta; Ploski, Rafal; Grajkowska, Wieslawa; Pronicki, Maciej (Folia Neuropathologica, 2014)
Dysferlinopathies are rare disorders of muscle that present two main phenotypes: Miyoshi myopathy with primarily distal weakness and limb-girdle muscular dystrophy type 2B (LGMD2B) with primarily proximal weakness. They are caused by mutations in the gene encoding the skeletal muscle protein dysferlin, which is involved in muscle repair. The clinical presentation of the disease is rather uncharacteristic, and molecular genetic testing is long-lasting; thus muscle biopsy may be essential in the diagnostic process. Histology itself reveals non-specific changes, but a variety of currently available muscle protein immunostains may be very helpful. We present a 19-year-old girl with epilepsy and elevated creatine phosphokinase (CPK) concentration. Due to increased CPK, myopathy was suspected and muscle biopsy was performed. Light microscopy showed no distinctive myopathic changes, and electron microscopy showed no abnormalities. Extended immunohistochemistry, performed much later, showed complete absence of dysferlin immunostaining. Based on that result, the diagnosis of LGMD2B was made, with subsequent genetic testing to be done. Two known pathogenic variants were found in the DYSF gene, confirming the diagnosis of LGMD2B and allowing proper genetic counseling.